2008
DOI: 10.1208/s12249-008-9082-4
|View full text |Cite
|
Sign up to set email alerts
|

Wax-incorporated Emulsion Gel Beads of Calcium Pectinate for Intragastric Floating Drug Delivery

Abstract: Abstract. The purpose of this study was to prepare wax-incorporated pectin-based emulsion gel beads using a modified emulsion-gelation method. The waxes in pectin-olive oil mixtures containing a model drug, metronidazole, were hot-melted, homogenized and then extruded into calcium chloride solution. The beads formed were separated, washed with distilled water and dried for 12 h. The influence of various types and amounts of wax on floating and drug release behavior of emulsion gel beads of calcium pectinate wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 23 publications
(30 reference statements)
2
35
0
Order By: Relevance
“…The emulsion gel calcium pectinate beads could float immediately with no lag time and remained floating for 8 h (Sriamornsak et al, 2008) as shown in Figure 8. The beads floated with an oil amount of 30% (w/w).…”
Section: Floating Time (Floating Behavior)mentioning
confidence: 94%
See 3 more Smart Citations
“…The emulsion gel calcium pectinate beads could float immediately with no lag time and remained floating for 8 h (Sriamornsak et al, 2008) as shown in Figure 8. The beads floated with an oil amount of 30% (w/w).…”
Section: Floating Time (Floating Behavior)mentioning
confidence: 94%
“…The floating properties of the emulsion gel beads may be attributed to the low-apparent density of the beads containing oils (Sriamornsak et al, 2004). This implied that the beads will have the tendency to exhibit a good in-vivo floating effect (Sriamornsak et al, 2008).…”
Section: Floating Time (Floating Behavior)mentioning
confidence: 99%
See 2 more Smart Citations
“…Thirawong, Nunthanid, Puttipipatkhachorn, & Sriamornsak, 2007;Thirawong, Thongborisute, Takeuchi, & Sriamornsak, 2008), as a carrier for floating drug delivery (e.g. Sriamornsak, Thirawong, & Puttipipatkhachorn, 2005;Sriamornsak et al, 2008), and as a carrier for colonic drug delivery (e.g. Sriamornsak, 1999;Sriamornsak, Nunthanid, Wanchana, & Luangtana-anan, 2003), etc.…”
Section: Introductionmentioning
confidence: 99%